Acid ion modification in a dialysis fluid - I. L. Poz; A. G. Strokov (Вестник трансплантологии и искусственных органов)
Apart from its main electrolytes – sodium, potassium, calcium and magnesium – a dialysis fluid (DF) contains a buffer for correction of acidosis. A small amount of acid is added to the DF to prevent calcium and magnesium precipitation. Acetic acid has traditionally been used for this purpose. Several studies have shown that acetate ion, even in small concentrations, can cause a number of adverse events, such as low blood pressure, production of proinflammatory cytokines, etc. This literature review aims at considering alternative acidic components of DF, such as citric, hydrochloric, and succinic acids, as well as their advantages, possibilities and features of their use in wide clinical practice.